O, say can you see? : American symbols and landmarks - Keenan, Sheila (Scholastic Reference, 2004)
Explains the history and importance of important places such as Plymouth Rock, Ellis Island, Mount Rushmore, the monuments in Washington, D. C., objects such as the Flag, Seal, and Liberty Bell, important documents, and holidays.